Greening the Scrap Metal Value Chain through Promotion of BAT/BEP to Reduce U-POP Releases from Recycling Facilities: Policy and Regulatory Framework - Pongpiachan, Siwatt; Apiratikul, Ronbanchob; Sutummakid, Niramon; Phothiruk, Darika; Jomsri, Pijitra; Buachan, Pantita (Journal of Posthumanism, 2025)
Thailand has implemented a strong and comprehensive system of regulations to effectively handle substances that pose threats to health and the environment. This includes specific legislation that clearly defines the roles of the various entities involved. Nevertheless, although there are extensive rules that cover a wide range of pollution sources, there is a noticeable lack of legislation specifically aimed at controlling dioxin and furan emissions from scrap metal smelters, which have a considerable impact on pollution levels. In order to address this disparity, suggested legislative actions aim to classify scrap metal smelters as controlled sources of contamination and establish criteria for dioxin and furan discharges. The objective of these measures, which consist of three proposed legislations, is to implement stringent emission restrictions and encourage the use of Best Available Techniques and Best Environmental Practices (BAT/BEP) to effectively reduce the impact of emissions. The proposed laws have been refined through stakeholder engagements, which included representatives from the public and corporate sectors, academics, and NGOs. These consultations aimed to ensure that the laws conform with international norms and commitments outlined in the Stockholm Convention. Thailand has conducted thorough evaluations of laws and regulations related to the accidental release of unintentionally produced persistent organic pollutants (U-POPs) emissions, in addition to legislative initiatives. As a result, proposed PCDD/PCDF emissions standards have been developed based on extensive analysis of existing literature. The first step in managing PCDD/PCDFs in secondary metal production is to set emission standards for different types of metals. This is done to encourage scrap metal recycling facilities to report the presence of PCDD/PCDFs in flue gas emissions. In addition, it is recommended that the government encourage the utilization of BAT and BEP for industrial waste recycling in order to decrease the presence of PCDD/PCDFs in the remaining waste. The involvement of stakeholders has played a crucial role in improving the proposed emission limits, guaranteeing more stringent regulation and alignment with health risk evaluations. Furthermore, financial incentives are essential in stimulating efforts to reduce PCDD/PCDFs, and industrialized countries such as the EU provide low-interest loans and credit guarantees to encourage the adoption of cleaner production processes. In Thailand, effective methods like subsidies, fiscal incentives, and eco-labeling programs have been recommended as ways to encourage the adoption of BAT and BEP in different industrial sectors. In this study, the most favorable strategy aims to offer customized incentives to businesses in order to promote the adoption of BAT/BEP practices. These incentives include financial support, subsidies for certification, and training programs. These activities demonstrate Thailand’s dedication to reducing PCDD/PCDF emissions and adhering to global norms, thereby promoting environmental sustainability and safeguarding public health.